The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0034-72992008000100006
|View full text |Cite
|
Sign up to set email alerts
|

Anquilose da articulação têmporo-mandibular

Abstract: A anquilose pode ser definida como sendo a fusão das superfícies articulares e seu tratamento é um verdadeiro desafio devido à alta taxa de recorrência. OBJETIVO: Descrever seis casos clínicos tratados pela técnica da reconstrução articular, avaliar os resultados dessas cirurgias e fazer uma revisão da literatura. METODOLOGIA: A população estudada neste estudo retrospectivo foi obtida dos prontuários do hospital universitário e tinha que ter sido submetida a cirurgia para tratamento de anquilose por reconstruç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Thus, it will be exposed and described in this paper the tomographic characteristics of normality, morphological changes and pathological conditions most commonly found in the temporomandibular joint region, besides some relevant information. of fibrocartilage integrity, allows the entry of fibrous connective tissue in the joint which, subsequently, results in ossification, leading to fusion of the mandibular condyle to the articular surface of the bone temporal 7 . As for the tomographic image can be observed that the condyle is filled by temporal bone, and a hipodense area within the lesion, which represents a remaining interarticular disk 7 ( Figure 2).…”
Section: Clinical Casesmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, it will be exposed and described in this paper the tomographic characteristics of normality, morphological changes and pathological conditions most commonly found in the temporomandibular joint region, besides some relevant information. of fibrocartilage integrity, allows the entry of fibrous connective tissue in the joint which, subsequently, results in ossification, leading to fusion of the mandibular condyle to the articular surface of the bone temporal 7 . As for the tomographic image can be observed that the condyle is filled by temporal bone, and a hipodense area within the lesion, which represents a remaining interarticular disk 7 ( Figure 2).…”
Section: Clinical Casesmentioning
confidence: 99%
“…As for the tomographic image can be observed that the condyle is filled by temporal bone, and a hipodense area within the lesion, which represents a remaining interarticular disk 7 ( Figure 2). The TMJ ankylosis can be classified according to the type of tissue involved, bone, fibrous or fibro -osseous, or according to the location, intra-or extra -capsular 7 .…”
Section: Clinical Casesmentioning
confidence: 99%
See 3 more Smart Citations